National idea is basic of eternal country - Aisultanova, K. A. (Eurasian Journal of Philology Science and Education, 2018)
This article is told about the factors of influencing on the formation of the national idea and national identity. Paying attention to the idea and purpose of «Eternal county, historical dates and examples are given. The structure of the idea «The eternal country» by ancient Turks is discussed and the history of the legend prevalent among the Kazakh people, the image of the mythical historical figures are analyzed. Al-Farabi’s philosophical work «Honest city», Zhysip Balasagun’s poem «Happy Knowledge» are told, the opinions of scholars researching the nation’s history and literature, culture are given.